Shock markets trading lessons for volatile times - Webb, Alexander Robert 1988- (FT Press, 2013)
Don't fear crises: use them as opportunities to make money! Shock Markets shows traders and investors exactly how to do it -- with exceptional detail, not vague handwaving. Robert Webb and Alexander Webb offer meticulous breakdowns of recent crises, revealing how they impacted both individual stocks and the market as a whole -- and helping you create detailed game plans for profiting from future shocks. By fusing real-life trading examples with rigorous moment-by-moment analysis of price changes, they give you tools to survive and thrive in even the most volatile markets. This accessible, actionable book answers crucial questions like: What moves stock prices? What moves the overall market? How can you profit from understanding catalysts that precipitate sudden sharp changes in stock prices? From the actions of corporate executives to regulatory decisions, earnings announcements to merger deals, lawsuits to settlements, macroeconomic reports to the policy actions of foreign governments, seemingly remote factors can have a huge, sudden impact on stocks in today's interconnected markets. Shock Markets illuminates these catalysts, and demonstrates their shifting behavior during fads, fashions, bubbles, crashes, and market crises. The focus is completely practical: helping savvy traders uncover profit where others find only peril.
Includes bibliographical references and index. - Print version record
Keywords: Stocks; Stock exchanges; Risk management; Actions (Titres de société); Bourse; Gestion du risque; exchange (method of acquisition); stock exchanges; risk management